Effect of Cryopreservation Factors on Cytomorphologic and Structural Characteristics of Fetal Nerve Cells - Ostankov, M. V.; Lebedinets, D. B.; Porozhan, E. A.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2009)
The experimental data, obtained under comparative evaluation of the effect of cryopreservation factors on integrity and phenotypic characteristics of fetal nerve cells (FNCs) of 11 gestation days have been presented. It has been shown that FNC cryopreservation according to developed program provided the high integrity of structural-phenotypic characteristics of FNCs. Neuro- and glioblasts with higher percentage of integrity were more cryoresistant under freezing with 10% DMSO. These data correlated with the expression indices in cells of neurospecific proteins such as: nestin and glial fibrillar acid protein (GFAP) and also one of proteins of neurofilaments, Î²-tubulin. Whereas nestin is mainly immuno-morphological marker of neural stem/progenitor cells and GFAP is the â€œmarkerâ€ protein of glial cells it is supposed that selected cryopreservation protocols may be used as a â€œnaturalâ€ sorter, enabling the selection of neuronal stem/progenitor or glial cells.